AHNS series – Do you know your guidelines? Diagnosis and management of cutaneous squamous cell carcinoma. Issue 11 (21st September 2016) - Ow, Thomas J.; Wang, Heng Rui; McLellan, Beth; Ciocon, David; Amin, Bijal; Goldenberg, David; Schmalbach, Cecelia E.
Abstract: This article is the next installment of the series "Do You Know Your Guidelines" presented by the Education Committee of the American Head and Neck Society. Guidelines for the prevention, diagnosis, workup, and management of cutaneous squamous cell carcinoma (SCC) are reviewed. © 2016 Wiley Periodicals, Inc. Head Neck 38 : 1708–1716, 2016